Evaluasi Peranan Pejabat Lelang dalam Sistem Lelang di Indonesia - Dodi Setiawan; Miftakhul Huda (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The auction system in Indonesia is the process of selling goods or services through a bargaining method where potential buyers or bidders compete to obtain the goods or services by offering the highest price. In recent years, online auctions have become popular in Indonesia, allowing people to participate in auctions via online platforms. Some well-known online auction platforms in Indonesia are Bukalapak, Tokopedia, and special auction platforms such as Invaluable or Christie's. Auctions in Indonesian legislation are regulated by various laws and regulations covering aspects such as government auctions, property auctions, and general regulations regarding the auction process. The role of an auction in auction procedures in Indonesia usually involves several important tasks related to auction transactions. A auction can be asked to examine documents related to the auction process, including the auction agreement, sale and purchase agreement, and other related documents. The aim of this research is to explain the evaluation of the role of auctions in the auction system in Indonesia. The approach used in this research is a juridical-empirical approach. The results of the research in this paper show that evaluating the role of notaries in the auction system in Indonesia can involve several aspects related to integrity, transparency, and legal compliance in the auction process. Meanwhile, the evaluation must include the extent to which the auction ensures that the auction process complies with applicable laws and regulations in Indonesia. The auction must accurately and independently certify the auction transaction. The evaluation should check whether they have performed this role well. It is important to evaluate the accuracy of the documents prepared by the auction, including the auction deed and other records that record the details of the auction transaction. In addition, the evaluation must consider whether the auction has helped in increasing transparency in the auction process, especially in terms of announcements, access to information, and reporting of auction results.